2022
DOI: 10.1055/s-0042-1742315
|View full text |Cite
|
Sign up to set email alerts
|

Nipple-sparing Mastectomy with Immediate Implant-based Reconstruction for Patients with Pure Ductal Carcinoma in Situ

Abstract: Objective The presence of an extensive intraductal component is associated to an increasing risk of relapse in the nipple-areola complex. The aim of the present study was to evaluate the outcomes of patients diagnosed with ductal carcinoma in situ (DCIS) who underwent nipple-sparing mastectomy (NSM) with immediate breast reconstruction using silicone implants. Methods We retrospectively analyzed the postoperative complications and oncological safety of 67 breast cancer patients diagnosed with pure DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…However, tissue behind the nipple was collected during the operation, which affected the blood supply of the nipple to some extent. As shown in several studies, NSM with IIBR usually contribute to nipple and skin ischemic necrosis 28,29 . In this study, 5 patients showed partial ischemic necrosis of the nipple after the operation.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, tissue behind the nipple was collected during the operation, which affected the blood supply of the nipple to some extent. As shown in several studies, NSM with IIBR usually contribute to nipple and skin ischemic necrosis 28,29 . In this study, 5 patients showed partial ischemic necrosis of the nipple after the operation.…”
Section: Discussionsupporting
confidence: 57%
“…As shown in several studies, NSM with IIBR usually contribute to nipple and skin ischemic necrosis. 28,29 In this study, 5 patients showed partial ischemic necrosis of the nipple after the operation. Fortunately, these wounds healed spontaneously after scabbing, and there was no nipple loss.…”
Section: Discussionmentioning
confidence: 62%